Thin-Film Phase Plates for Transmission Electron Microscopy Fabricated from Metallic Glasses. (29th September 2016) - Dries, Manuel; Hettler, Simon; Schulze, Tina; Send, Winfried; Müller, Erich; Schneider, Reinhard; Gerthsen, Dagmar; Luo, Yuansu; Samwer, Konrad
Abstract: Thin-film phase plates (PPs) have become an interesting tool to enhance the contrast of weak-phase objects in transmission electron microscopy (TEM). The thin film usually consists of amorphous carbon, which suffers from quick degeneration under the intense electron-beam illumination. Recent investigations have focused on the search for alternative materials with an improved material stability. This work presents thin-film PPs fabricated from metallic glass alloys, which are characterized by a high electrical conductivity and an amorphous structure. Thin films of the zirconium-based alloy Zr65.0 Al7.5 Cu27.5 (ZAC) were fabricated and their phase-shifting properties were evaluated. The ZAC film was investigated by different TEM techniques, which reveal beneficial properties compared with amorphous carbon PPs. Particularly favorable is the small probability for inelastic plasmon scattering, which results from the combined effect of a moderate inelastic mean free path and a reduced film thickness due to a high mean inner potential. Small probability plasmon scattering improves contrast transfer at high spatial frequencies, which makes the ZAC alloy a promising material for PP fabrication.